Comparación de los niveles de logro del rendimiento académico en el área Personal Social de los niños y niñas del quinto grado de primaria de las Instituciones Educativas Nº 00654 y 00813 del distrito de Rioja en el año 2007. - Aguila Isuiza, Lito Ronald Del (2009)
The education is par excellence the social phenomenon formulated by the man to forge its evolution, based on that vision, the governments give each country they should be you consent of that condition, of such a form that its directionality is to guarantee a level of lite worthy to the citizens; the education is the most effective means to achieve it. Where has taken this aspect seriously the basic education it is obligatory in practically the entirety gives the advanced countries, being recognized this way the that all the citizens are entitled to this very social one" (Santín, s/f). However the access to the education in a social group where marked differences exist of development, to reach these purposes of equality of gives educational opportunities it was necessary to have a sistema universal, obligatory and gratuitous education (Darcy, 1969). Good part of this tradition it presupposes that the problem of the poverty it is a hereditary problem; that the main reason for which sorne people finish richer than others it is because they developed bigger cognitive dexterities and that the school can reduce the cognitive inequalities substantially of the population. From the point of gives view of the educational theory, the controversy it is centered in wondering, if the man is the result of his first experiences or of the school experiences. Who proclaim for a central paper of the educational sistema in the achievement of an equality in the development of the cognitive dexterities, they place a li the importance in the school stage that is to say in the period between the 7 and the 18 years of age. Historically the public or popular concept has been exaggerated the public education, since in its origin it is an essentially oriented institution toward the strata means and high. Historically where considerable homogeneity has existed social class, give religion or give antecedent ethnic, the schools have been effective in terms of results (Charles, 1970). Is defined as effective school to that educational institution that promotes of durable form the integral development of all and singular of their students, beyond what would be foregone having in it counts their initial yield and their social, cultural and economic situation" (CIES, 2005). In many studieses of mensuration of the educational quality, fundamentally in those that have associated the social factors to the school results they have determined that in South America the results of the educational process they are strongly influenced by the socioeconomic level of the families and for rising, of the school establishment (Donoso and Hawes, 2000). This influence has cultural impacts in turn, what explains the force synergy that you/they have the socioeconomic variables on the rest of the school variables, including of the administration of the establishments (Alvariño, 2001). The reality of the poor schools that at the same time •suffer the inattention of the administrativa entities of the state to be in the most secret places of our homeland, of our region or in the border zones of our town, the educational results don't finish reflecting the indicators of the prospective educational quality. The precarious conditions associated to the social problem generalized in these means, the educational one has many difficulties to achieve learnings totally satisfactory, on the contrary, these they possess marked limitations. Therefore it is logical to assert that notables differences exist among in the level of learning that you/they are achieved in the students of the urban schools and the level of learning that is achieved in the schools of gives marginal urban and urban areas. They are the reasons that impelled us to carry out an investigation to establish the existent differences clearly and to clarify the real levels among the possibilities of learning that the students present of the educational institutions of our town. After processing the results, the evidences put to the light the tendency of the influence of the social factors in the quality of the learning the students that were reflected in the difference among the achievements the academic yield of the students of the educational institutions of the urban area that was bigger to the yield achieved by the children and girls of the educational institutions of the marginal urban area. These evidences should be constant concern of the educational agents of our town so that, in a frank social commitment, efforts are articulated to forge a significant improvement of the educational quality in all our schools, affirming the road toward to the real democratization of the education in our country